2023
DOI: 10.1021/acs.jpclett.3c00504
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Comprehensive Understanding of Photocatalysis: What Systematic Studies and Alcohol Surface Chemistry on TiO2(110) Have to Offer for Future Developments

Abstract: Heterogeneous photocatalytic systems are usually described based on electrochemistry, which the vast majority of interpretations and strategies for optimizing photocatalysts rely on. Charge carrier dynamics are usually in the spotlight, whereas the surface chemistry of the photocatalyst is neglected. This is unjustified, because studies on alcohol photoreforming on metal-decorated rutile single crystals revealed that the electrochemical reaction model is not generally applicable. Hence, many photocatalytic rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The strict separation of half reactions, often made in photocatalysis, is thus not applicable in that case. 19,58,59 However, we observed a strong dependence of the reaction kinetics on the presence of water being the H + transport medium, and for the Pt loading an optimum Pt amount for every photocatalytic system was derived. 9 Additionally, EPR measurements indicated that Pt NPs capture photogenerated electrons supporting the commonly accepted mechanism of H + reduction at the surface of Pt NPs after surface migration via hydroxyl groups being favored in the presence of water.…”
Section: Resultsmentioning
confidence: 85%
“…The strict separation of half reactions, often made in photocatalysis, is thus not applicable in that case. 19,58,59 However, we observed a strong dependence of the reaction kinetics on the presence of water being the H + transport medium, and for the Pt loading an optimum Pt amount for every photocatalytic system was derived. 9 Additionally, EPR measurements indicated that Pt NPs capture photogenerated electrons supporting the commonly accepted mechanism of H + reduction at the surface of Pt NPs after surface migration via hydroxyl groups being favored in the presence of water.…”
Section: Resultsmentioning
confidence: 85%
“…The depicted reaction pathways are strongly simplified and still under debate. [2,31] increased, whereas the selectivity toward the valuable products formaldehyde and methyl formate decreased. In comparison to earlier reports on the synergistic effect of temperature and light in thermally assisted photocatalytic reactions using Ru/TiO 2 , [8] Cu/TiO 2 , [9] or Pt/TiO 2 [2] photocatalysts, the influence of light irradiation is significant for the conditions used here.…”
Section: Resultsmentioning
confidence: 99%
“…Thermocatalytic and photocatalytic reactions are marked in red and green, respectively. The depicted reaction pathways are strongly simplified and still under debate [2,31].…”
mentioning
confidence: 99%